Analisis Peran dan Tugas Badan Penasihatan Pembinaan Perkawinan (BP4) dalam Membina Rumah Tangga: Studi Kasus di KUA Bogor Selatan - Abduloh, Fauzan Ridho; Mukri, Syarifah Gustiawati; Kosim, Ahmad Mulyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research analyzes the roles and duties of Badan Penasihatan Pembinaan dan Pelestarian Perkawinan (BP4) in fostering families, with a case study focus on the Kantor Urusan Agama (KUA) Bogor Selatan. BP4, under the Ministry of Religious Affairs, was established to reduce the high divorce rate in Indonesia. The objective of this research is to understand how BP4 performs its roles and duties in fostering families at the KUA Bogor Selatan and to identify the challenges it faces. The research employs a qualitative approach with field study. Data were collected through BP4 Musyawarah Nasional (MUNAS), observations, in-depth interviews with relevant parties at the KUA Bogor Selatan, documentation, and literature studies. The research findings show that BP4 at the KUA Bogor Selatan carries out its roles and duties in providing pre-marital guidance and helping to resolve family conflicts according to the provisions of the BP4 XVI MUNAS in 2019. However, BP4 has not been fully optimal in mediating couples seeking divorce due to a lack of coordination with the Religious Court. In conclusion, the implementation of BP4's roles and duties at the KUA Bogor Selatan has not been optimal because there are still roles and duties in the provisions of the XVI National Meeting in 2019 that have not been realized. This research is expected to contribute to the development of policies and practices for family guidance at the KUA Bogor Selatan.